Perceptual strategies of pigeons to detect a rotational centre--a hint for star compass learning? - Bianca Alert; Andreas Michalik; Sascha Helduser; Henrik Mouritsen; Onur Güntürkün (PLoS ONE, 2015)
Birds can rely on a variety of cues for orientation during migration and homing. Celestial rotation provides the key information for the development of a functioning star and/or sun compass. This celestial compass seems to be the primary reference for calibrating the other orientation systems including the magnetic compass. Thus, detection of the celestial rotational axis is crucial for bird orientation. Here, we use operant conditioning to demonstrate that homing pigeons can principally learn to detect a rotational centre in a rotating dot pattern and we examine their behavioural response strategies in a series of experiments. Initially, most pigeons applied a strategy based on local stimulus information such as movement characteristics of single dots. One pigeon seemed to immediately ignore eccentric stationary dots. After special training, all pigeons could shift their attention to more global cues, which implies that pigeons can learn the concept of a rotational axis. In our experiments, the ability to precisely locate the rotational centre was strongly dependent on the rotational velocity of the dot pattern and it crashed at velocities that were still much faster than natural celestial rotation. We therefore suggest that the axis of the very slow, natural, celestial rotation could be perceived by birds through the movement itself, but that a time-delayed pattern comparison should also be considered as a very likely alternative strategy.